Genome‐wide association studies of toxicity to oxaliplatin and fluoropyrimidine chemotherapy with or without cetuximab in 1800 patients with advanced colorectal cancer. Issue 9 (31st July 2021) - Watts, Katie; Wills, Christopher; Madi, Ayman; Palles, Claire; Maughan, Timothy S.; Kaplan, Richard; Al‐Tassan, Nada A.; Kerr, Rachel; Kerr, David; Gray, Victoria; West, Hannah; Houlston, Richard S.; et al.
Abstract: Chemotherapies administered at normal therapeutic dosages can cause significant side‐effects and may result in early treatment discontinuation. Inter‐individual variation in toxicity highlights the need for biomarkers to personalise treatment. We sought to identify such biomarkers by conducting 40 genome‐wide association studies, together with gene and gene set analyses, for any toxicity and 10 individual toxicities in 1800 patients with advanced colorectal cancer treated with oxaliplatin and fluoropyrimidine chemotherapy ± cetuximab from the MRC COIN and COIN‐B trials (385 patients received FOLFOX, 360 FOLFOX + cetuximab, 707 XELOX and 348 XELOX + cetuximab). Single nucleotide polymorphisms (SNPs), genes and gene sets that reached genome‐wide or suggestive significance were validated in independent patient groups. We found that MROH5 was significantly associated with neutropenia in MAGMA gene analyses in patients treated with XELOX ( P  = 6.6 × 10 −7 ) and was independently validated in those receiving XELOX + cetuximab; pooled P  = 3.7 × 10 −7 . rs13260246 at 8q21.13 was significantly associated with vomiting in patients treated with XELOX (odds ratio = 5.0, 95% confidence interval = 3.0‐8.3, P  = 9.8 × 10 −10 ) but was not independently replicated. SNPs at 139 loci had suggestive associations for toxicities and lead SNPs at five of these were independently validated (rs6030266 with diarrhoea, rs1546161 with hand‐foot syndrome, rs9601722 with neutropenia, rs13413764 with lethargy and rs4600090 with nausea; all with pooled P 's < 5.0 × 10 −6 ). In conclusion, the association of MROH5 with neutropenia and five other putative biomarkers warrant further investigation for their potential clinical utility. Despite our comprehensive genome‐wide analyses of large, well‐characterised, clinical trials, we found a lack of common variants with modest effect sizes associated with toxicities. Abstract : What's new? Among cancer patients, toxic side effects of chemotherapeutic agents can vary considerably. This inter‐individual variability may be influenced by genetic factors. Here, genome‐wide association studies were analysed for toxicities to oxaliplatin and fluoropyrimidine chemotherapy (FOLFOX and XELOX) in patients with advanced colorectal cancer. In XELOX‐treated patients, MROH5 variants were strongly associated with neutropenia. The variant rs13260246, mapped to SLC26A7, was associated with vomiting. Suggestive associations for toxicities were identified for single nucleotide polymorphisms (SNPs) at 139 loci; 5 of which validated. The validated variants could serve as predictive biomarkers for specific chemotherapy‐related toxicities.